Exploring the Role of Chemokine Receptor 6 (Ccr6) in the BXD Mouse Model of Gulf War Illness - Gao, Jun; Xu, Fuyi; Starlard-Davenport, Athena; Miller, Diane B.; O’Callaghan, James P.; Jones, Byron C.; Lu, Lu (Frontiers in Neuroscience, 2020)
Gulf War illness (GWI) is a chronic and multi-symptomatic disorder with persistent neuroimmune symptomatology. By using RNA-seq data of prefrontal cortex (PFC) from 31 BXD recombinant inbred (RI) strains and their parental strains (C57BL/6J and DBA/2J) under three chemical treatment groups—saline control (CTL), diisopropylfluorophosphate (DFP), and corticosterone combined with diisopropylflurophosphate (CORT+DFP), we identified Ccr6 as a candidate gene underlying individual differences in susceptibility to GWI. The Ccr6 gene is cis-regulated and its expression is significantly correlated with CORT+DFP treatment. Its mean transcript abundance in PFC of BXD mice decreased 1.6-fold (p < 0.01) in the CORT+DFP group. The response of Ccr6 to CORT+DFP is also significantly different (p < 0.0001) between the parental strains, suggesting Ccr6 is affected by both host genetic background and chemical treatments. Pearson product-moment correlation analysis revealed 1473 Ccr6-correlated genes (p < 0.05). Enrichment of these genes was seen in the immune, inflammation, cytokine, and neurological related categories. In addition, we also found five central nervous system-related phenotypes and fecal corticosterone concentration have significant correlation (p < 0.05) with expression of Ccr6 in the PFC. We further established a protein-protein interaction subnetwork for the Ccr6-correlated genes, which provides an insight on the interaction of G protein-coupled receptors, kallikrein-kinin system and neuroactive ligand-receptors. This analysis likely defines the heterogeneity and complexity of GWI. Therefore, our results suggest that Ccr6 is a promising GWI biomarker.